2020
DOI: 10.1177/1550147720912958
|View full text |Cite
|
Sign up to set email alerts
|

Autoregressive integrated moving average model–based secure data aggregation for wireless sensor networks

Abstract: Nodes in a wireless sensor network are normally constrained by hardware and environmental conditions and face challenges of reduced computing capabilities and system security vulnerabilities. This fact calls for special requirements for network protocol design, security assessment models, and energy-efficient algorithms. Data aggregation is an effective energy conservation technique, which removes redundant information from the data aggregated from neighbor sensor nodes. How to further improve the effectivenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A set of equations is proposed to perform predictive analysis using specific algorithms and models, such as ARIMA (Autoregressive Integrated Moving Average) [ 34 ], to assess and quantify relevant metrics in the field. These processes will facilitate decision-making and increase situational awareness within threat intelligence.…”
Section: Design and Implementation Of The Security Framework For Assu...mentioning
confidence: 99%
“…A set of equations is proposed to perform predictive analysis using specific algorithms and models, such as ARIMA (Autoregressive Integrated Moving Average) [ 34 ], to assess and quantify relevant metrics in the field. These processes will facilitate decision-making and increase situational awareness within threat intelligence.…”
Section: Design and Implementation Of The Security Framework For Assu...mentioning
confidence: 99%
“…When processing a large amount of data and data in the same direction, the wireless sensor network under ZigBee technology can effectively avoid the collision time of multiple data. It can resend the data after detecting the data transmission problem [ 36 ]. Therefore, ZigBee technology has a strong application capability, and the system also guarantees the security of data transmission.…”
Section: Analysis Of Embedded Cloud Computing Data Monitoring System ...mentioning
confidence: 99%
“…Moreover, authors have reported that proper Cluster Head selection is also considered as promising technique which can minimize the energy depletion. The authors in [30] have focused on improving the data aggregation process along with security concerns in the Wireless Sensor Networks (WSN). This scheme uses a novel secure data aggregation scheme where autoregressive model is used for time series analysis.…”
Section: Data Aggregationmentioning
confidence: 99%